(untitled) (OverHolland, 2018)
Delft University of Technology has a large, varied set of buildings in all kinds of forms and styles, distributed over an extensive campus. The buildings at Eindhoven University of Technology are typologically and architecturally homogeneous, and located closer together. The Eindhoven university was founded in the 1960s; the Delft university has a longer history, and hence an older stock of buildings. So what exactly are the differences and similarities between the Delft and Eindhoven buildings? Is there a typical ‘Delft’ and a typical ‘Eindhoven’ type of building? To what extent has the university of technology programme changed over the years, and do the old buildings differ from the new ones? And what issues arise when existing university buildings have to be reassigned to new purposes? These questions will be examined in the light of three comparative case studies on the basis of analytical drawings.